Finding a balance in reduced toxicity hematopoietic stem cell transplantation for thalassemia: role of infused CD3+ cell count and immunosuppression - Meissner, Barbara; Greil, Johann; Kafa, Kinan (Bone marrow transplantation, 2024)
We performed a retrospective analysis on 124 patients with transfusion-dependent thalassemia who were registered in the German pediatric registry for stem cell transplantation. All patients underwent first allogeneic hematopoietic stem cell transplantation (HSCT) between 2011 and 2020 and belonged mainly to Pesaro risk class 1–2. Four-year overall (OS) and thalassemia-free survival (TFS) were 94.5% ± 2.9% and 88.0% ± 3.4% after treosulfan-fludarabine-thiotepa- and 96.9% ± 3.1% (P = 0.763) and 96.9% ± 3.1% (P = 0.155) after busulfan-fludarabine-based conditioning. Mixed chimerism below 75% occurred predominantly in treosulfan-based regimens (27.5% versus 6.2%). OS and TFS did not differ significantly between matched sibling, other matched family and matched unrelated donor (UD) HSCTs (OS: 100.0%, 100.0%, 96.3% ± 3.6%; TFS: 96.5% ± 2.4%, 90.0% ± 9.5%, 88.9% ± 6.0%). However, mismatched UD-HSCTs performed less favorable (OS: 84.7% ± 7.3% (P = 0.029); TFS: 79.9% ± 7.4% (P = 0.082)). We generated a scoring system reflecting the risk to develop mixed chimerism in our cohort. The main risk-reducing factors were a high CD3+ cell count (≥6 × 107/kg) in the graft, busulfan-conditioning, pre-conditioning therapy and low-targeted ciclosporin A trough levels. Acute GvHD grade III-IV in treosulfan-based concepts predominantly occurred in patients with UD and reduced GvHD prophylaxis but not in the context of high CD3+ cell doses. Taken together, this information might be used to develop more risk-adapted HSCT regimens for thalassemia patients.
Gesehen am 28.06.2024